Acute gonadotropin-releasing hormone agonist treatment enhances extinction memory in male rats. (August 2017) - Maeng, L.Y.; Taha, M.B.; Cover, K.K.; Glynn, S.S.; Murillo, M.; Lebron-Milad, K.; Milad, M.R.
Graphical abstract: Highlights: GnRH agonist Lupron treatment acutely elevates serum testosterone (T) levels. T elevation during extinction training improves extinction memory recall. Freezing during recall is negatively correlated with IL and CeL c-fos activity. Endogenous T modulation by Lupron influences fear extinction neurocircuitry. Abstract: Leuprolide acetate (LEU), also known as Lupron, is commonly used to treat prostate cancer in men. As a gonadotropin-releasing hormone (GnRH) receptor agonist, it initially stimulates the release of gonadal hormones, testosterone (T) and estradiol. This surge eventually suppresses these hormones, preventing the further growth and spread of cancer cells. Individuals receiving this treatment often report anxiety and cognitive changes, but LEU's effects on the neural mechanisms that are involved in anxiety during the trajectory of treatment are not well known. In this study, we examined the acute effects of LEU on fear extinction, hypothesizing that increased T levels following a single administration of LEU will facilitate extinction recall by altering neuronal activity within the fear extinction circuitry. Two groups of naïve adult male rats underwent a 3-day fear conditioning, extinction, and recall experiment. The delayed group (n = 15) received a single injection of vehicle or LEU (1.2 mg/kg) 3 weeks before behavioral testing. The acute group (n = 25) received an injection one day after fear conditioning, 30 min prior to extinction training. Following recall, the brains for all animals were collected for c-fos immunohistochemistry. Blood samples were also collected and assayed for T levels. Acute administration of LEU increased serum T levels during extinction training and enhanced extinction recall 24 h later. This enhanced extinction memory was correlated with increased c-fos activity within the infralimbic cortex and amygdala, which was not observed in the delayed group. These results suggest that the elevation in T induced by acute administration of LEU can influence extinction memory consolidation, perhaps through modification of neuronal activity within the infralimbic cortex and amygdala. This may be an important consideration in clinical applications of LEU and its effects on anxiety and cognition.